Case Report - Infection of Total Knee Arthroplasty Treated with One-Stage Surgery and Linezolid - A. M. Dell'Aquila; C. Janovsky; M. Cohen (Journal of Bone and Joint Infection, 2017)
Staphylococcus spp meticillin resistant infection can be treated with Linezolid. This is a case report of an orthopaedic implant infection in a 60 year-old male treated orally with Linezolid and Rifampicin for three months after one-stage arthroplasty. This is possible provided that platelet count is closely monitored throughout the course of treatment.